2013
DOI: 10.1016/j.infbeh.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal attention-directing strategies in 9-month-old infants attaining joint engagement

Abstract: Coordinated Joint Engagement (CJE) is a behavioral measure used in the infant-caregiver interaction paradigm to measure joint attention. To know how mothers scaffold infant attention to prompt joint engagement states, this study attempted to determine (a) which specific maternal Attention-Directing Strategies facilitate CJE in mother-infant interactions and (b) how Attention-Directing Strategies precede a range of infant engagement states. Free play in 33 low-SES dyads was analyzed sequentially, a method that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…; Mendive et al . ). Towards the end of the first year, the child begins to be able to start and coordinate himself/herself episodes of joint attention, by using gaze, pointing gestures and facial expressions, to signal his/her intentions (Liszkowski et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…; Mendive et al . ). Towards the end of the first year, the child begins to be able to start and coordinate himself/herself episodes of joint attention, by using gaze, pointing gestures and facial expressions, to signal his/her intentions (Liszkowski et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, infant social engagement with parents has been well-characterized in studies of typical development (e.g., Feldman, Greenbaum, and Yirmiya, 1999; Tamis-LaMonda, Bornstein, and Baumwell, 2001), thereby providing a logical focus for possible early markers of autism in high risk infant siblings. Research on parent-infant interaction demonstrates that typically-developing children engage enthusiastically with their parents during shared play activities, both initiating interaction and responding to parents’ scaffolding and teaching (e.g., Bigelow et al, 2010; Bornstein, Tamis-LaMonda, Hahn, and Haynes, 2008; Mendive, Bornstein, and Sebastian, 2013). In contrast, lower levels of social interest, social engagement, and the use of communicative gestures have been identified in retrospective studies of infants who later received an autism diagnosis (Osterling, Dawson, and Munson, 2002; Werner, Dawson, Munson, and Osterling, 2005), underscoring the importance of prospective studies of early social engagement in HR infant siblings.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of verbal scaffolding quality have been found to be positively related to preschoolers' EF skills in general (Hammond, Müller, Carpendale, Bibok, & Liebermann-Finestone, 2012), and to AC and EF components specifically. Several longitudinal studies have demonstrated that scaffolding quality predicts WM and cognitive flexibility (Bernier, Carlson, & Whipple, 2010;Conway & Stifter, 2012;Hughes & Ensor, 2009;Matte-Gagné & Bernier, 2011), while in cross-sectional studies scaffolding has been observed to be related to enhanced AC, inhibitory control and cognitive flexibility (Bibok, Carpendale, & Müller, 2009;Hopkins, Lavigne, Gouze, LeBailly, & Bryant, 2013;Mendive, Bornstein, & Sebastián, 2013). This study focuses on verbal scaffolding aspects.…”
mentioning
confidence: 98%